2012
DOI: 10.1007/s00109-012-0986-9
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell HIF-1α regulates asthma airway resistance and eosinophil function

Abstract: Hypoxia-inducible factor (HIF)-1α is a master regulator of inflammatory activities of myeloid cells, including neutrophils and macrophages. These studies examine the role of myeloid cell HIF-1α in regulating asthma induction and pathogenesis, and for the first time, evaluate the roles of HIF-1α and HIF-2α in the chemotactic properties of eosinophils, the myeloid cells most associated with asthma. Wild-type (WT) and myeloid cell-specific HIF-1α knockout (KO) C57BL/6 mice were studied in an ovalbumin (OVA) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 31 publications
4
44
0
1
Order By: Relevance
“…Using an ovalbumin-induced (OVA-induced) asthma model, others have shown that myeloid HIF-1α deficiency reduces airway hyperresponsiveness and eosinophil infiltration. Furthermore, HIF-1α and HIF-2α directly regulate eosinophil chemotaxis in opposing ways (150). Therefore, the role of myeloid HIF-1α in airway diseases remains very complex, and varies in different experimental models.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…Using an ovalbumin-induced (OVA-induced) asthma model, others have shown that myeloid HIF-1α deficiency reduces airway hyperresponsiveness and eosinophil infiltration. Furthermore, HIF-1α and HIF-2α directly regulate eosinophil chemotaxis in opposing ways (150). Therefore, the role of myeloid HIF-1α in airway diseases remains very complex, and varies in different experimental models.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…Under sterile conditions alveolar (AMϕs) and peritoneal (PMϕs) were isolated by bronchoalveolar lavage and peritoneal lavage from naïve mice utilizing cold SF RPMI1640 medium, as described in detail previously [24][25][26]. In some studies, mice were subjected to thermal stress as previously described [27].…”
Section: Animal Studiesmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] This suggests a distinct function of HIF in innate and adaptive immunity. 18 Myeloid HIF-1a, for instance, is essential in myeloid cell-mediated inflammation and enhances the bactericidal capacity of phagocytes. 13,19 In addition, mice deficient in HIF-1a in myeloid cells develop less severe LPS-induced sepsis.…”
Section: Introductionmentioning
confidence: 99%